Eksistensi Pesantren Nahdlatul Wathan sebagai Agen Perubahan Sosial Keagamaan di Lombok - Lenny Herlina (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
The province of NTB has a beautiful island which in 2017 was named a World Halal Tourism Destination. The island is known as the